Amalan Etika Pekerja Khidmat Manusia dan Hubungan dengan Kepuasan Kerja - Muhamad Dzahir, Kasa (2003)
This study looked at the relationship between the perception of human service worker towards social work profession's ethical behavior with unethical behavior and job satisfaction. The study postulated that if a human service worker perceived and behaved ethically in the context of human service profession, he or she will also experience job satisfaction in the work that they do. The ascertain this relationship, this study was carried out at the state and regional welfare office, state and regional hospitals, Serenti Centers, state National Drug Agencies and NGO's. The location of this study is in the states of Kedah, Perlis and Pulau Pinang. The samples for the study are social workers at NGO's. The study employs a cross-sectional survey design and uses a questionnaire developed by Mahmood and Muhammad Dzahir based the American National Social Work Association's Code of Ethical Guideline. This code consisted of six domains which are relationship to clients, peers, practice, the professional status, the profession of social worker and society. A total of 62.23% out of 278 responded to the study. The main findings of the study includes a positive relationship between the perception of ethical behavior and incidence towards ethical behavior, however there are no relationships between the perception towards ethical behavior and the age of respondents and no difference in the these perception among respondents of different professional background (social worker, counselors, rehabilitation officer ets.). Male respondents stated a higher perception towards positive ethical behavior as compared to the female respondents, but there are is a significant relationship between positive perceptions towards social work professional ethics and job satisfaction. Implications to ethical theories and the practice of ethical behavior were discuss with focus given to the training and developmental aspects for human service workers.